Therapeutic Non-equivalence of Digoxin Tablets in United Kingdom: Correlation with Tablet Dissolution Rate. Issue 5895 (29th December 1973) - Shaw, T. R. D.; Raymond, K.; Howard, M. R.; Hamer, John
Abstract : Seven types of digoxin 0·25 mg tablet in common use in the United Kingdom were administered to a total of 38 patients. Significant differences were found in the mean plasma digoxin levels and in the control of atrial fibrillation achieved with these brands. There was a close correlation between the dissolution rate of the tablets and the plasma digoxin levels. Measurement of in-vitro dissolution rate appears to be a valid method of ensuring that different tablets of digoxin are of equal efficacy. However, in some patients absorption of the drug is markedly sensitive to changes in dissolution rate and new pharmacopoeal standards should not be defined until very rapidly-dissolving formulations have been studied.